Challenges associated with implementing anti-doping policy and programs in Africa - Ruwuya, Jonathan; Juma, Byron Omwando; Woolf, Jules (Frontiers in Sports and Active Living, 2022)
·Concerns regarding the capability of the International Olympic Committee to address doping in sport catalyzed the formation of WADA in 1999. ·In its establishment phase, WADA sought geopolitical legitimacy and support from national governments for financing and acceptance. ·Africa was not considered during WADA’s creation, relegating African states to a passive role in the global anti-doping program, and yet is still subject to the strict compliance requirements for WADA’s global policy. ·African countries face challenges establishing anti-doping support structures and implementing the universal policy, including macro-level policy demands that favor addressing legacies of colonialism and human capacity development. ·To develop robust anti-doping support structures and capacity for policy implementation, African nations must spearhead anti-doping initiatives by leveraging existing infrastructure and encouraging collaborations between NADOs.